UNDERSTANDING LEADERSHIP AND EMPOWERMENT IN THE WORKPLACE - Michael Ba, Banutu-Gomez (European Scientific Journal, ESJ, 2015)
Employee empowerment becomes more important in organizations as management styles have shifted to a focus on numerous leaders rather than supervisors within business world. It is a leader’s responsibility to motivate and engage their followers in their work, and can accomplish this through empowering their employees. The topic of employee empowerment has been well explored, and has a clear impact on worker’s performance. This research aims to examine how the empowerment an employee feels they have can affect how they view their leader. The results revealed a correlation in workers opinion of their leader and their perceived level of empowerment; except when it comes to the decision making process. In addition, an overwhelming amount of employees reported that communication with their leader is strained and that is something they would like to strengthen. These findings provide significant insight for leaders, emphasizing the importance of including employees in decision-making processes and establishing clear, honest and open communication with their followers.